4D cardiac magnetic resonance imaging, 4D and 2D transthoracic echocardiography: a comparison of in-vivo assessment of ventricular function in rats. (April 2019) - Stegmann, Hedwig; Bäuerle, Tobias; Kienle, Katharina; Dittrich, Sven; Alkassar, Muhannad
Preclinical cardiovascular research is the foundation of our understanding and broad knowledge of heart function and cardiovascular disease. Reliable cardiac imaging modalities are the basis for applicable results. Four-dimensional cardiac magnetic resonance (4D CMR) has been set as the gold standard for in-vivo assessment of ventricular function in rodents. However, technical improvements in echocardiography now allow us to image the whole heart, which makes four-dimensional echocardiography (4DE) a possible alternative to 4D CMR. To date, no study has systematically assessed 4DE in comparison with 4D CMR in rats. In total we studied 26 juvenile Sprague-Dawley rats (Crl: CD (SD) IGS). Twenty rats underwent echocardiographic imaging (2D and 4D) and 4D CMR. Five of those rats underwent a ligation of the superior and inferior vena cava to reduce the cardiac inflow as a disease model. Six additional rats were used to assess reproducibility of echocardiography and underwent three echocardiographic examinations. 4D CMR was performed on a 7T scanner; 2D and 4D echocardiography was conducted using a 40 MHz transducer. Correlation between 4D CMR, 4DE and 2DE for left-ventricular ejection fraction (LVEF) was assessed. An excellent correlation was observed between 4DE and 4D CMR ( r  = 0.95, p  < 0.001). Correlation of 2DE and 4D CMR was weak ( r  = 0.57, p  < 0.01). 4DE provides results that are equally precise as 4D CMR and highly reproducible with less technical effort than 4D CMR.